BERMAIN PLAYDOUGH TERHADAP KEMAMPUAN MOTORIK HALUS ANAK AUTIS DI SDLB - Yunia Wardah, Erika (Jurnal Pendidikan Khusus, 2017)
ABSTRACT This research was formed the background by the important of developing fine motoric ability of autism children. The fine motoric ability of autism children often experienced disturbance. It appeared to the autism children’s ability in SDLBN Tompokersan Lumajang in holding, pressing, grasping, and pinching things so they required to be developed. Through playing playdough the autism children were actively stimulated to develop their fine motoric ability and gave them freedom to do various activities in playing playdough as forming and printing. This research had purpose to prove the influence of playing playdough toward the fine motoric ability of autism children in SDLBN Tompokersan Lumajang. This research used quantitative approach with pre-experimental design kind, and the research arrangement was one group pre test post test design. The subject in this research was 6-7 years old autism children in SDLBN Tompokersan Lumajang numbering 7 children whose fine motoric ability still required to be developed. The data collection technique used statistic non parametric with wilcoxon match pair test. The research result indicated that there was value enhancement of fine motoric ability of autism children during the early observation or pre test was 60,92 to be 84,25 in the end of observation or post test. Beside that the research result also indicated Zh = 2,36 was greater than Zt = 1,96 with critic value 5% (two sides test). If Z counted > Z table (2,36 > 1,96) it indicated that there was influence of playing playdough toward fine motoric ability of autism children in SDLBN Tompokersan Lumajang.   Keywords: playdough, fine motoric